The chromatin-remodeling protein ATRX is critical for neuronal survival during corticogenesis. - Bérubé, N; Mangelsdorf, M; Jagla, M; Vanderluit, J; Garrick, D; Gibbons, R; Higgs, D; Slack, R; Picketts, D (2005)
Mutations in genes encoding chromatin-remodeling proteins, such as the ATRX gene, underlie a number of genetic disorders including several X-linked mental retardation syndromes; however, the role of these proteins in normal CNS development is unknown. Here, we used a conditional gene-targeting approach to inactivate Atrx, specifically in the forebrain of mice. Loss of ATRX protein caused widespread hypocellularity in the neocortex and hippocampus and a pronounced reduction in forebrain size. Neuronal "birthdating" confirmed that fewer neurons reached the superficial cortical layers, despite normal progenitor cell proliferation. The loss of cortical mass resulted from a 12-fold increase in neuronal apoptosis during early stages of corticogenesis in the mutant animals. Moreover, cortical progenitors isolated from Atrx-null mice undergo enhanced apoptosis upon differentiation. Taken together, our results indicate that ATRX is a critical mediator of cell survival during early neuronal differentiation. Thus, increased neuronal loss may contribute to the severe mental retardation observed in human patients.